"There's only one Man United?": How to make the most of former sporting brand leaders. Issue 6 (11th May 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – It has become something of a cliché to borrow cues from successful sporting managers and coaches and apply them to a modern business context. Indeed, many former managers are getting in on the act – see the success of some former coaches on the speaking circuit and even the increasing amount of work ex-Manchester United manager Sir Alex Ferguson has been doing with Harvard Business School. It seems that there is a lucrative life after all when it is time to hang up the whistle and clipboard. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.